Epigenotype–phenotype correlations in Silver–Russell syndrome. Issue 11 (3rd August 2010) - Wakeling, E L; Amero, S Abu; Alders, M; Bliek, J; Forsythe, E; Kumar, S; Lim, D H; MacDonald, F; Mackay, D J; Maher, E R; Moore, G E; Poole, R L; et al.
Abstract : Background: Silver–Russell syndrome (SRS) is characterised by intrauterine growth restriction, poor postnatal growth, relative macrocephaly, triangular face and asymmetry. Maternal uniparental disomy (mUPD) of chromosome 7 and hypomethylation of the imprinting control region (ICR) 1 on chromosome 11p15 are found in 5–10% and up to 60% of patients with SRS, respectively. As many features are non-specific, diagnosis of SRS remains difficult. Studies of patients in whom the molecular diagnosis is confirmed therefore provide valuable clinical information on the condition. Methods: A detailed, prospective study of 64 patients with mUPD7 (n=20) or ICR1 hypomethylation (n=44) was undertaken. Results and conclusions: The considerable overlap in clinical phenotype makes it difficult to distinguish these two molecular subgroups reliably. ICR1 hypomethylation was more likely to be scored as 'classical' SRS. Asymmetry, fifth finger clinodactyly and congenital anomalies were more commonly seen with ICR1 hypomethylation, whereas learning difficulties and referral for speech therapy were more likely with mUPD7. Myoclonus-dystonia has been reported previously in one mUPD7 patient. The authors report mild movement disorders in three further cases. No correlation was found between clinical severity and level of ICR1 hypomethylation. Use of assisted reproductive technology in association with ICR1 hypomethylation seems increased compared with the general population. ICR1 hypomethylation was also observed in affected siblings, although recurrence risk remains low in the majority of cases. Overall, a wide range of severity was observed, particularly with ICR1 hypomethylation. A low threshold for investigation of patients with features suggestive, but not typical, of SRS is therefore recommended.